Is the free market acceptable to everyone? - Clayton, Matthew; Stevens, David (Springer, 2015)
In this paper we take issue with two central claims that John Tomasi makes in Free Market Fairness (2012). The first claim is that Rawls’s difference principle can better be realized by free market institutions than it can be by state interventionist regimes such as property-owning democracy or liberal socialism. We argue that Tomasi’s narrow interpretation of the difference principle, which focuses largely on wealth and income, leaves other goods (such as control of the workplace and access to economic assets) worryingly unsatisfied. The second claim is that a wide set of economic liberties ought to be protected because they realize responsible ‘self-authorship.’ We argue that this claim also fails because, crucially, whether economic liberties serve individuals in pursuing their ambitions will depend on the nature of those ambitions and how the use of those liberties by others would affect their pursuit of them. If an expansion of liberty is good for us in some ways, but bad in others, we need to assess whether, all things considered, we would be better off with or without such expanded economic rights. We argue that the expansion Tomasi proposes is likely to fail this test.